2023
DOI: 10.1002/anie.202305651
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Decomposition of Perfluorocarbons for over 1000 Hours via Active Site Regeneration

Hang Zhang,
Tao Luo,
Yingkang Chen
et al.

Abstract: Tetrafluoromethane (CF4), the simplest perfluorocarbon (PFC), has the potential to exacerbate global warming. Catalytic hydrolysis is a viable method to degrade CF4, but fluorine poisoning severely restricts both the catalytic performance and catalyst lifetime. In this study, Ga is introduced to effectively assists the defluorination of poisoned Al active sites, leading to highly efficient CF4 decomposition at 600°C with a catalytic lifetime exceeding 1,000 hours. 27Al and 71Ga magic‐angle spinning nuclear mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…With the continuous depletion of non-renewable fossil fuels and increasing environmental pollution, finding green and renewable energy sources to replace fossil energy is critical to future energy sustainability and the global environment. 1–3 Hydrogen energy is considered to be an attractive sustainable energy with high mass energy density and zero-carbon nature. 4–7 Hydrogen production is an essential part of hydrogen energy.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous depletion of non-renewable fossil fuels and increasing environmental pollution, finding green and renewable energy sources to replace fossil energy is critical to future energy sustainability and the global environment. 1–3 Hydrogen energy is considered to be an attractive sustainable energy with high mass energy density and zero-carbon nature. 4–7 Hydrogen production is an essential part of hydrogen energy.…”
Section: Introductionmentioning
confidence: 99%
“…At present, various methods, including plasma, combustion, and catalytic hydrolysis, have been developed for the decomposition methods of CF 4 . Among them, catalytic hydrolysis is regarded as a promising method owing to its capability of high decomposition efficiency and large gas flux. Al-based materials with abundant acidic sites are the most used catalysts in decomposition of CF 4 . Song et al reported that the more the Lewis acid sites on the surface of Al-based catalysts, the stronger the ability to decompose CF 4 . Zhang et al found that the strong Lewis acid site of unsaturated tricoordinated Al (Al III ) was the main active site for CF 4 decomposition, indicating that more Al III active sites represent higher CF 4 decomposition activity.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive use of fossil fuels, such as coal, oil, and natural gas, has led to increased carbon dioxide emissions, resulting in significant environmental issues such as land desertification, sea level rise, and climate change. To address this challenge, converting CO 2 into fuels or high-value chemicals has been suggested as an ideal way to mitigate CO 2 emissions. Among various techniques, electrocatalytic CO 2 reduction reaction (CO 2 RR) has been identified as one of the most efficient and controllable methods, as it reduces not only CO 2 emissions but also human dependence on fossil fuels by utilizing low-grade renewable electricity . However, the CO 2 RR requires high energy to activate the nonpolar and chemically inert linear CO 2 molecule with CO bonds under ambient conditions. Additionally, the competition of hydrogen evolution reaction (HER) in aqueous CO 2 RR solution poses challenges to controlling product selectivity. , …”
Section: Introductionmentioning
confidence: 99%